Free Radical-Mediated Protein Radical Formation in Differentiating Monocytes - Prasad, Ankush; Manoharan, Renuka Ramalingam; Sedlářová, Michaela; Pospíšil, Pavel (International journal of molecular sciences, 2021)
Free radical-mediated activation of inflammatory macrophages remains ambiguous with its limitation to study within biological systems. U-937 and HL-60 cell lines serve as a well-defined model system known to differentiate into either macrophages or dendritic cells in response to various chemical stimuli linked with reactive oxygen species (ROS) production. Our present work utilizes phorbol 12-myristate-13-acetate (PMA) as a stimulant, and factors such as concentration and incubation time were considered to achieve optimized differentiation conditions. ROS formation likely hydroxyl radical (HO●) was confirmed by electron paramagnetic resonance (EPR) spectroscopy combined with confocal laser scanning microscopy (CLSM). In particular, U-937 cells were utilized further to identify proteins undergoing oxidation by ROS using anti-DMPO (5,5-dimethyl-1-pyrroline N-oxide) antibodies. Additionally, the expression pattern of NADPH Oxidase 4 (NOX4) in relation to induction with PMA was monitored to correlate the pattern of ROS generated. Utilizing macrophages as a model system, findings from the present study provide a valuable source for expanding the knowledge of differentiation and protein expression dynamics.
Keywords: tetradekanoylforbolacetát; tvar buňky; HL-60 cells; proteiny; macrophages; viabilita buněk; Tetradecanoylphorbol Acetate; phorbol 12-myristate 13-acetate; hydroxylový radikál; acetofenony; NADPH oxidase; Hydroxyl Radical; Cell Proliferation; HL-60 buňky; monocyty; U-937 cells; buněčná diferenciace; Cell Survival; Electron Spin Resonance Spectroscopy; elektronová paramagnetická rezonance; Acetophenones; lidé; NOX4; HL-60 Cells; Humans; barvení a značení; Free Radicals; Monocytes; U937 Cells; protein-centered radicals; proliferace buněk; NADP; Staining and Labeling; volné radikály; Cell Shape; Proteins; Cell Differentiation; U937 buňky